Fabry‐Perot Interferometer Observations of Thermospheric Horizontal Winds During Magnetospheric Substorms. Issue 5 (22nd May 2019) - Cai, L.; Oyama, S.; Aikio, A.; Vanhamäki, H.; Virtanen, I.
Abstract: The high‐latitude ionosphere‐thermosphere system is strongly affected by the magnetospheric energy input during magnetospheric substorms. In this study, we investigate the response of the upper thermospheric winds to four substorm events by using the Fabry‐Perot interferometer at Tromsø, Norway, the International Monitor for Auroral Geomagnetic Effects magnetometers, the EISCAT radar, and an all‐sky camera. The upper thermospheric winds had distinct responses to substorm phases. During the growth phase, westward acceleration of the wind was observed in the premidnight sector within the eastward electrojet region. We suggest that the westward acceleration of the neutral wind is caused by the ion drag force associated with the large‐scale westward plasma convection within the eastward electrojet. During the expansion phase, the zonal wind had a prompt response to the intensification of the westward electrojet (WEJ) overhead Tromsø. The zonal wind was accelerated eastward, which is likely to be associated with the eastward plasma convection within the substorm current wedge. During the expansion and recovery phases, the meridional wind was frequently accelerated to the southward direction, when the majority of the substorm WEJ current was located on the poleward side of Tromsø. We suggest that this meridional wind acceleration is related to a pressure gradient produced by Joule heating within the substorm WEJ region. In addition, strong atmospheric gravity waves during the expansion and the recovery phases were observed. Key Points: Ion drag plays an important role in acceleration of the zonal wind during substorms Eastward acceleration of the zonal wind is associated with intensification of westward electrojet during the expansion and recovery phases Observed meridional wind acceleration may be produced by pressure gradient caused by the Joule heating